Analisis Inovasi Layanan Digital Micropay Mobile dalam Meningkatkan Kepuasan Anggota (Studi di BMT Artha Buana Metro) - Zevi Lusiana; Ika Trisnawati Alawiyah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
The rapid development of digital technology has encouraged Islamic microfinance institutions to innovate their services in order to enhance efficiency and member satisfaction. This study aims to analyze the implementation of the Micropay Mobile digital service innovation and its impact on member satisfaction at BMT Artha Buana Metro. The research employs a descriptive qualitative method with a field research approach. Data were collected through observation, in-depth interviews, and documentation, using triangulation to ensure validity. The findings reveal that Micropay Mobile, developed from the previous IBS Mobile platform, has improved member satisfaction through four key aspects: ease of access anytime and anywhere, efficiency in time and transaction costs, real-time transaction speed and accuracy, and a multi-layered security system based on PIN authentication and transaction notifications. SERVQUAL analysis indicates that the application fulfills five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Challenges include limited digital literacy and internet connectivity constraints. To address these issues, the institution provides socialization programs, user education, and face-to-face assistance. The study confirms that digital transformation strategically strengthens long-term relationships based on trust and loyalty.